2009
DOI: 10.3354/meps08106
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition and diet inferences of abyssal macrourids in the eastern North Pacific

Abstract: The lipid compositions of 2 abyssal macrourids, Coryphaenoides armatus and C. yaquinae, from the eastern North Pacific were examined and used to infer diet. The resulting fatty acid (FA) profiles are the first published for C. yaquinae and among the first for abyssal fishes. They indicated a greater proportion of polyunsaturated FAs and lower monounsaturated FAs than shallower living congeners, suggestive of homeoviscous adaptations to great pressure. Cholesterol was the predominant sterol, which is frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…FA trophic markers have long been recognized as efficient tools in studies of marine food webs (Sargent et al 1989, Budge et al 2002, 2006, Dalsgaard et al 2003. Recent studies have demonstrated that FAs can be successfully used to elucidate feeding ecology and trophic relationships of marine fish (Drazen et al 2009, Stowasser et al 2009) and invertebrates (Silina & Zhukova 2009, Spilmont et al 2009). However, northern/temperate and abyssal marine ecosystems have been the focus of most research efforts, and FA data regarding trophic interactions in tropical marine ecosystems are scarce (reviewed by Dalsgaard et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…FA trophic markers have long been recognized as efficient tools in studies of marine food webs (Sargent et al 1989, Budge et al 2002, 2006, Dalsgaard et al 2003. Recent studies have demonstrated that FAs can be successfully used to elucidate feeding ecology and trophic relationships of marine fish (Drazen et al 2009, Stowasser et al 2009) and invertebrates (Silina & Zhukova 2009, Spilmont et al 2009). However, northern/temperate and abyssal marine ecosystems have been the focus of most research efforts, and FA data regarding trophic interactions in tropical marine ecosystems are scarce (reviewed by Dalsgaard et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the diet of deep sea species using more direct methods is problematic because the pressure changes experienced as animals are brought to the surface frequently causes regurgitation or stomach eversion, precluding analysis of stomach contents (e.g. sea stars, Howell et al 2003; macrourid fishes, Drazen et al 2009). Relative abundances of several diet-derived FAs varied among 7 species of deep sea holuthurians from the northeast Atlantic, suggesting a diversity of feeding modes or niches (Ginger et al 2000).…”
Section: Deep Sea and Hydrothermal Vent Food Websmentioning
confidence: 99%
“…FAs are useful in habitats where direct observation would pose significant challenges, such as the deep sea (Howell et al 2003, Drazen et al 2009). FA tracers are also used to determine the fate of primary production, especially in habitats where the dominant primary producer is not directly consumed by the dominant herbivores (Meziane & Tsuchiya 2000, Kharlamenko et al 2001.…”
Section: Fa Analysis Of Benthic Food Websmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the lipid accumulation strategy is unknown for deep-sea skates, which rival squaloids as the deepest chondrichthyans. In comparison, deep-sea teleosts such as macrourids store liver lipids as metabolic fuel rather than for buoyancy, so they have TAG-rich livers with negligible DAGE or squalene (Drazen, 2007;Drazen et al, 2009). …”
Section: Buoyancy Through Hydrostatic Lift: Lipid Accumulation In Livermentioning
confidence: 99%